Mengintegrasikan Nilai-Nilai Budaya Indonesia Dan Nilai-Nilai Teori Realita Dalam Menghadapi Kelompok LGBT - Muliasari, Mona; Lacksana, Indra; Sari, Nurul Enggar Permana (Universitas Muria Kudus, 2018)
Lesbian, Gay, Bisexual and Transgender (LGBT) issues are currently being addressed internationally, including Indonesia, especially since the decision of the United States Supreme Court to pass a federal Marriage Act in 2015. The rolling out of LGBT issues in Indonesia has contributed to conflicting opinions between the pros and cons of various parties, both civil society, government officials, even academics to religious leaders. The current flow of literature continues to be dominated by arguments that do not characterize the personality of the Indonesian nation as a country that upholds moral values and religious values that cause the counselor in Indonesia to be wary in addressing multicultural issues in general and LGBT issues in particular.